Sol-gel synthesis and characterisation of (Nd, Cr) co-doped BiFeO3 nanoparticles. Issue 17 (21st November 2016) - Vanga, Pradeep Reddy; Mangalaraja, R.V.; Ashok, M.
ABSTRACT: Bi0.95 Nd0.05 Fe1– x Cr x O3 ( x = 0, 0.01, 0.03, 0.05) samples are synthesised by the sol-gel method. The variation in structure, magnetisation, electrical and photocatalytic properties by Cr doping at Fe site in Bi0.95 Nd0.05 FeO3 samples is analysed. X-ray diffraction pattern confirms the formation of rhombohedral structure in all the samples. The crystallite size is calculated using the Scherrer relation and found to be in nanometre range. Kubelka-Munk theory is used to determine the direct band gap of the samples from reflectance spectra. The saturation magnetisation is found to enhance the concentration of chromium. Arrott-Belov-Kouvel plot confirms the ferromagnetic nature in the samples. The leakage mechanisms are studied to understand the influence of Cr concentration on the BFO. A good correlation exists between the leakage current and ferroelectric behaviour. Photocatalytic tests show degradation of methylene blue dye in the presence of H2 O2 . A drastic decrease in photocatalytic activity is observed with the concentration of Cr.